(untitled) (The Journal of Theoretical Accounting Research, 2026)
This study examines the impact of India’s National Education Policy (NEP) 2020 on the employability transitions of accounting graduates, with a specific focus on how educational reforms shape their readiness for the profession. Through a quantitative research design, the study gathered data from 400 higher education students and recent graduates in the National Capital Region (NCR), Delhi. It identifies key educational elements-multidisciplinary learning, vocational exposure, and industry alignment-that influence employability outcomes for accounting graduates. The findings highlight the central role of multidisciplinary education in developing core accounting skills such as professional judgment, analytical thinking, and adaptability to evolving industry demands. While vocational training and industry-oriented learning contribute to employability, their impact is secondary to the effect of multidisciplinary learning. This research advances accounting education theory by proposing a framework that integrates these key educational factors into accounting curricula. It emphasizes the theoretical implications of NEP 2020 reforms and their potential to enhance employability outcomes. The study offers valuable insights for policymakers and educational institutions aiming to optimize curriculum design and improve accounting graduate preparedness, aligning education with professional and industry needs.